1990
DOI: 10.1128/jb.172.5.2236-2240.1990
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an active fragment of the LasA protein from Pseudomonas aeruginosa: enhancement of elastase activity

Abstract: A 22-kilodalton protein purified from the culture supernatant fraction of Pseudomonas aeruginosa (strains PA220 and PAO1) was found to enhance the elastolytic activity of purified P. aeruginosa elastase. N-terminal sequence analysis identified the protein as a fragment of the lasA gene product (P. A. Schad and B. H. Iglewski, J. Bacteriol. 170:2784Bacteriol. 170: -2789Bacteriol. 170: , 1988. However, comparative analysis with the reported LasA sequence indicated that the purified LasA fragment is longer than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…Although purified LasA alone does not show high elastolytic activity, culture filtrates of lasA mutants (e.g. PAO-E64 and FRD2128) show much less elastolytic activity (30 -90%) when compared with their respective wild type strains (8,10,11,16). Peters and Galloway (11) examined this further with purified components and showed that the elastolytic activity of elastase (10 g input) increased 25-fold in the presence of purified LasA (10 g input), which is a LasA/ elastase molar ratio of ϳ1.7.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although purified LasA alone does not show high elastolytic activity, culture filtrates of lasA mutants (e.g. PAO-E64 and FRD2128) show much less elastolytic activity (30 -90%) when compared with their respective wild type strains (8,10,11,16). Peters and Galloway (11) examined this further with purified components and showed that the elastolytic activity of elastase (10 g input) increased 25-fold in the presence of purified LasA (10 g input), which is a LasA/ elastase molar ratio of ϳ1.7.…”
Section: Resultsmentioning
confidence: 96%
“…LasA Enhancement of Elastase Activity-LasA has been shown to enhance the elastolytic activity of Pseudomonas elastase in a dose-dependent manner (11). However, the effect has only been shown with high elastase input (10 g) and a relatively narrow range of LasA/elastase molar ratios (0.1 to 1.7, 0.5-10 g of LasA).…”
Section: Resultsmentioning
confidence: 99%
“…It can also activate the host kinin cascade to cause inflammation (11). The elastolytic activity of elastase is enhanced by the product of the lasA gene (7,24,26) which has recently been demonstrated in and purified from culture supernatants of P. aeruginosa (24).…”
mentioning
confidence: 97%
“…LasA protease (staphylolysin) (7) has high staphylolytic activity that results from cleavages of the pentaglycine cross-linkages within the peptidoglycan of Staphylococcus aureus cells (8). LasA protease can also nick elastin at certain Gly-Gly sequences (9,10), an activity that increases the susceptibility of elastin to other proteases and contributes to the elastinolytic potential of P. aeruginosa (9,11,12). The fourth endopeptidase secreted by P. aeruginosa (lysine-specific endopeptidase; protease IV) cleaves peptide bonds on the carboxyl side of lysine residues in peptides and proteins and can act on a number of host proteins including complement components, IgG, and fibrinogen (13)(14)(15).…”
mentioning
confidence: 99%